Diagnóstico de la responsabilidad social empresarial (rse) en las empresas del sector comercio del cantón Latacunga – Cotopaxi - Llumiquinga Gualotuña, Evelyn Mishell (2022)
The importance of corporate social responsibility (CSR) is currently a determining factor for the management of companies, in this sense, this research project aimed to determine the degree of CSR in commercial companies in the canton of Latacunga, province of Cotopaxi. A field research methodology was used in which a convenience sampling was carried out and 8 commercial companies were selected (Riego System, Dipag, Secohi, Semayari, Multisa, ASSA Chevrolet, Centro Ferretero "San Agustín and the commercial area of Novacero), to which the Ethos questionnaire was applied, which is based on the analysis of the following dimensions: Values, Transparency and Corporate Governance; Internal Public; Environment; Suppliers, Consumers and Customers; Community and finally Government and Society. The veracity of the questionnaire was checked using IBMSPSS software, which yielded a Cronbach's Alpha of 0.909, which determined that the instrument was reliable. For data processing, an average percentage was established for each dimension, making it possible to measure the degree of CSR, as well as to determine its value using a classification scale in which Stage 1 corresponds to a very low value of responsibility and Stage 4 to a high value. The results indicate that the Semayari company is in Stage 1, which corresponds to a very low level; the companies Riego System, Dipag, Multisa and Centro Ferretero "San Agustín" are in Stage 2, corresponding to a low level; the company Secohi is in Stage 3, moderate level; and the companies SSA Chevrolet and the commercial area of Novacero are in Stage 4, high level. It is concluded that the company ASSA Chevrolet with a percentage of 86% is in favorable compliance with each dimension, achieving sustainable operations.